Energy Storage: Porous One‐Dimensional Nanomaterials: Design, Fabrication and Applications in Electrochemical Energy Storage (Adv. Mater. 20/2017). Issue 20 (May 2017) - Wei, Qiulong; Xiong, Fangyu; Tan, Shuangshuang; Huang, Lei; Lan, Esther H.; Dunn, Bruce; Mai, Liqiang
Abstract : In article number1602300, Bruce Dunn, Liqiang Mai, and co‐workers present an overview of emerging novel, porous, one‐dimensional nanostructures: from methodologies for rational and controllable synthesis to their successful application in different types of energy‐storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium–oxygen batteries, and supercapacitors.